40 tahun Kitab Hukum Kanonik Gereja Katolik Latin (1983-2023). Historisitas – Amandemen – Analisis - Galed, Daniel Ortega (Forum, 2024)
The actual CIC of the Latin Catholic Church is 40 years old this year since it was first promulgated by Pope John Paul II on January 25, 1983. In its journey as universal law of the Latin Catholic Church, during three pontificates, all Popes have made amendments to it. This study intends to canonically analyze any juridical modifications or amendments sought by the Church Legislator regarding certain themes in the Codex. To get a more holistic context, as in the sub-title, the historical panorama of the birth of the ecclesiastical juridical system will first be synthesized. Then, all the modifications to universal law over the past 40 years, whether promulgated through Apostolic Letters in the form of motu proprio or in Apostolic Constitutions, will be presented. The purpose of this paper is to find the spirit and orientation behind the “revitalization” of the canonical norms in question, which must be in line with the ultimate goal of Church Law, namely the realization of the “salvation of the souls”.